Pengaruh Motivasi Kerja dan Kompetensi terhadap Kualitas Layanan Polisi di Sentra Pelayanan Kepolisian Terpadu (SPKT) Polsek Berastagi - Bela Maghfira Tarigan; Supriadi, Supriadi (Yayasan Literasi Sains Indonesia, 2025)
The formulation of the problem in this research what is the effect of work motivation on service quality, what is the effect of competence on service quality, what is the effect of work motivation and competence on service quality at Sentra Pelayanan Kepolisian Terpadu (SPKT) Polsek Berastagi. This research to find out and analyze the effect of work motivation on service quality, to find out and analyze the effect of competence on service quality, to find out and analyze the effect of work motivation and competence on service quality at Sentra Pelayanan Kepolisian Terpadu (SPKT) Polsek Berastagi. The methods used in this research are validity test, reliability test, classical assumption test, linear regression, and hypothesis testing. Data is measured or processed using SPSS, with a sample using a questionnaire distributed to 37 employess at Sentra Pelayanan Kepolisian Terpadu (SPKT) Polsek Berastagi. The results of this research indicate that the variable work motivation effect positive and significant on service quality. The competence variable effect positive and significant on service quality. Variables work motivation and competence effect positive and significant on service quality.